Strategic innovation policies and the emergence of new clusters: the comparative experience of the binational Medicon Valley - Maria Del Carmen Sanchez Carreira; Xavier Vence Deza; Óscar Rodil Marzábal (European Regional Science Association (ERSA), 2010)
Medicon Valley is a bi-national life science cluster located in the √òresund region. This cross-boder region includes a Swedish side and a Danish one. The fact of being a bi-national cluster constitutes a remarkable singularity. This life science cluster is the third in Europe and among the top five in the world. Their outstanding strongholds are the quality of scientific research; the technology transfer and knowledge sharing between universities, hospitals and industries; the innovative and business environment; and the access to capital, mainly through venture capital. Such strongholds are the result of a combination of factors. The universities (mainly, Lund and Copenhagen Universities) and the long tradition of pharma industry are considered the initital drivers. The cooperation among all the agents seems to be other key element of the cluster. In fact, this experience is considered a successful example of the triple helix model. Furthermore, we have also to consider the role of public policies. Public agencies (as Vinnova) and later organizations as Medicon Valley Alliance are also relevant actors. The paper is focused on the strategic innovation policies that helped to the emergence of this cluster. The main aim is the comparation between the implemented policies in both national sides of the cluster. Moreover, an assessment of the results in the two areas is attempted. One outstanding characteristic of the policy instruments implemented to support innovation and specifically biotechnology in both countries is the systemic perspective. Moreover, a lot of the implemented policy instruments addressed to various policy goals. Most of the policies implemented were generic to stimulate innovation, mainly at the time of the emergence of the cluster. However, some specific measures also exist. The role of policy has been increasing at time of developing the cluster, with a broad use of biotechnology focused instruments.
Keywords: 330